Sosialisasi Pencegahan Stunting di Dusun Muteran Desa Kejagan, Kecamatan Trowulan, Kabupaten Mojokerto - Firza Farianshah Difandra; Ahmad Yanuar Bahri; Imam Mahmudah; Rinawati Dewi; Yasmine Azalia Wandana; Chaterine Br Tarigan; Hanani Nazua; Cinta Tunggal Rahmadhani; Anggy Kinaya Putri; Sukina Sukina; Yanda Bara Kusuma (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stunting remains a significant public health challenge in Indonesia, especially in rural areas. The national stunting prevalence was recorded at 24.4% in 2021, still far above the maximum threshold of 14% set in the SDGs for 2024. To tackle this problem, the KKN-T Bela Negara Group 8 team of the National Development University